Long-term Prognosis of Acute-on-Chronic Liver Failure Survivors. Issue 2 (February 2019) - Yoon, Eileen L.; Kim, Tae Yeob; Lee, Chang Hyeong; Kim, Tae Hun; Cho, Hyun Chin; Lee, Sang Soo; Kim, Sung Eun; Kim, Hee Yeon; Kim, Chang Wook; Song, Do Seon; Yang, Jin Mo; Sinn, Dong Hyun; et al.
Abstract : Goals: We aimed to investigate significant factors influencing the long-term prognosis of patients who survived acute-on-chronic liver failure (ACLF). Background: The mortality of ACLF is predominantly affected by the organ failure severity. However, long-term outcomes of patients who survive ACLF are not known. Study: A cohort of 1084 cirrhotic patients who survived for more than 3 months following acute deterioration of liver function was prospectively followed. ACLF was defined by the European Association for the Study of the Liver Chronic Liver Failure Consortium definition. Results: The mean follow-up duration was 19.4±9.9 months. In the subgroup of patients without previous acute decompensation (AD), ACLF occurrence did not affect long-term outcomes. However, in patients with previous AD, ACLF negatively affected long-term transplant-free survival even after overcoming ACLF (hazard ratio, 2.00, P =0.012). Previous AD was the significant predictive factor of long-term mortality and was independent of the Model for End-stage Liver Disease score in these ACLF-surviving patients. Organ failure severity did not affect transplant-free survival in patients who survived an ACLF episode. Conclusions: A prior history of AD is the most important factor affecting long-term outcomes following an ACLF episode regardless of Model for End-stage Liver Disease score. Prevention of a first AD episode may improve the long-term transplant-free survival of liver cirrhosis patients.